Using the methodology of subject-language integrated learning in the process of teaching English in an innovative school - Mazhit, Z.; Abdankyzy, L.; Sarsembayeva, A.B. (KU Publ., 2021)
The article is focused on the consideration of the advantages of the technology of subject-language integrated learning (CLIL) and the problems of its use in English lessons in an innovative school. Currently in Kazakhstan the most popular secondary educational institutions are schools with in-depth study of subjects in English, the essential difference of which is the attitude to educational innovations, the search for new models of education, the creation of fundamentally new educational information. An important role in this is played by the choice of the optimal teaching method. In this capacity the generally recognized technology of integrated teaching of a language and a subject, known as the CLIL technology, is used. This teaching method is the study of a certain science using a second or third language, mastering the language in a subject, achieving subject and language goals. In the course of applying CLIL, learning English becomes more focused, as it is used to develop specific communicative and sociocultural competencies. In addition, by working on various topics, students learn specific terms, replenishing their vocabulary with subject terminology, which prepares them for further study of subjects in English and successful dialogue in various fields of activity. An important place is occupied by the selection of educational material, which depends on the structure and specifics of the subject, which, in turn, requires professionalism from the teacher and a constant search for new methodological solutions. When compiling assignments, the teacher should take into account the specifics of language forms, include exercises for the development of four types of speech activity (reading, listening, writing, speaking), use various types of assessment to stimulate independent and creative activity of students, as well as increase their motivation.
Инновациялық мектепте ағылшын тілін оқытуда пəндік-тілдік кіріктірілген оқыту əдістемесін қолдану
Использование методики предметно-языкового интегрированного обучения в процессе преподавания английского языка в инновационной школе
Keywords: subject-language integrated learning; English; innovative schools; technology; teaching material; communicative competencies; language goals; four types of speech activity